Recurrent Tubal Ectopic Pregnancy - Sidra Khan; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Ectopic pregnancy (EP) is one of the most common gynecological emergency and carries the highest proportion of first trimester mortalities. Apart from fetal loss, significant maternal mortality and morbidity, recurrence of ectopic pregnancy and impairment of subsequentfertility is also of concern. Wereport a rare case of a patient without any risk factors who had EP three times in her life. Every time our management was based on the clinical condition of the patient, site of ectopic gestation, patient's future fertility desire and available expertise in the hospital. These factors should be the standard managementprotocols while managing such patients. Key Words: Pregnant Females, Ectopic Pregnancy, Emergency Therapeutic Laparoscopy.